Thirty Years of Transformation in Post-Soviet Higher Education: Outcomes and Lessons - Smolentseva, Anna (International Higher Education, 2023)
This article provides an overview of the transformations of higher education in 15 post-Soviet countries since 1991. Post-Soviet transformations were part of the global shift that prioritized individual goods/values over collective goods/values, and a natural and spontaneous economic order over political action. Neoliberal transformations have contributed to social inequalities in post-Soviet societies and higher education systems. The commodification of knowledge has led to the erosion of its intrinsic value.